High incidence of avascular necrosis in adolescents with acute lymphoblastic leukaemia: a UKALL XII analysis. - Patel, B; Richards, S; Rowe, J; Goldstone, A; Fielding, A (2008)
Avascular necrosis (AVN) is a serious complication of acute lymphoblastic leukaemia (ALL) therapy. Little is known of the scope and magnitude of this problem among adults with ALL. We analysed the incidence and risk factors for AVN in 1053 patients on the UKALLXII/ECOG2993 study. AVN affected 99 joints in 42 patients at a median of 2.2 years post-diagnosis, giving a crude incidence rate of 4.0%. Statistically significant risk factors for the development of AVN were age and treatment with chemotherapy. Patients receiving prolonged chemotherapy without stem cell transplant were at significantly greater risk of developing AVN than stem cell transplant recipients (P<0.00005). The actuarial incidence of AVN was 29% at 10 years in patients <20 years old compared to 8% at 10 years in those >20 years old; P=0.0004; odds ratio 0.28 (95% CI=0.14-0.56).